SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA ASN BALITBANG KEMENTERIAN PERTAHANAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Fahrurozi, Azil; Novitasari, Dini; Kurniawan, Riza (Universitas Krisnadwipayana, 2025)
The rapid development of science and technology in government presents a unique challenge for any institution. One form of change is the realization of transparent and democratic governance. One element of government administration that requires attention in reform efforts is the arrangement of government apparatus or apparatus, which includes the arrangement of bureaucratic institutions, systems and the arrangement of existing human resource management. Performance assessment itself is an assessment based on performance planning at the individual, unit, or organizational level, taking into account targets, achievements, results, and benefits achieved. The purpose of creating a decision support system for the performance assessment of State Civil Apparatus (ASN) is to achieve objectivity in employee assessments based on achievement and career systems.